Too Little or Too Much? Untangling the Relationship between Corporate Philanthropy and Corporate Financial Performance - WANG, Heli (Institutional Knowledge at Singapore Management University, 2008)
What is the relationship between corporate philanthropy and corporate financial performance? Some scholars argue that corporate philanthropy facilitates stakeholder cooperation and helps secure access to critical resources controlled by those stakeholders, suggesting that corporate philanthropy should be positively associated with corporate financial performance. In contrast, other scholars take a negative stance, suggesting that corporate philanthropy diverts valuable corporate resources and tends to inhibit corporate financial performance. Existing empirical studies have not found conclusive evidence on the corporate philanthropy-financial performance relationship. Integrating and extending existing perspectives, this study develops the argument that the relationship between corporate philanthropy and financial performance is best captured by an inverse U-shape. In addition, it posits that the inverse U-shaped relationship varies with the level of dynamism in firms' operational environment. Using a panel data set of 817 firms listed in the Taft Corporate Giving Directory from 1987 to 1999, we find strong support for these arguments.